2012
DOI: 10.1111/j.1365-2966.2011.20337.x
|View full text |Cite
|
Sign up to set email alerts
|

On the theory of disc photoevaporation

Abstract: We discuss a hydrodynamical model for the dispersal of protoplanetary discs around young, low mass (<1.5 M_sun) stars by photoevaporation from the central object's energetic radiation, which considers the far-ultraviolet as well as the X-ray component of the radiation field. We present analytical scaling relations and derive estimates for the total mass-loss rates, as well as discussing the existence of similarity solutions for flows from primordial discs and discs with inner holes. Furthermore, we perform num… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

14
379
4

Year Published

2014
2014
2018
2018

Publication Types

Select...
4
3

Relationship

3
4

Authors

Journals

citations
Cited by 296 publications
(397 citation statements)
references
References 89 publications
(262 reference statements)
14
379
4
Order By: Relevance
“…Kenyon & Hartmann 1995;Luhman et al 2010;. Such observed twotimescale behaviour has favoured the development of disc dispersal models that involve a rapid disc clearing phase, contrary to the predictions of simple viscous draining, and in agreement with photoevaporation (Clarke et al 2001;Alexander et al 2006a;Alexander et al 2006b;Ercolano 2008;Ercolano et al 2009;Gorti et al 2009;Owen et al 2010;Owen et al 2011b;Owen et al 2012) or possibly planet formation (Armitage & Hansen 1999).…”
Section: Introductionmentioning
confidence: 73%
“…Kenyon & Hartmann 1995;Luhman et al 2010;. Such observed twotimescale behaviour has favoured the development of disc dispersal models that involve a rapid disc clearing phase, contrary to the predictions of simple viscous draining, and in agreement with photoevaporation (Clarke et al 2001;Alexander et al 2006a;Alexander et al 2006b;Ercolano 2008;Ercolano et al 2009;Gorti et al 2009;Owen et al 2010;Owen et al 2011b;Owen et al 2012) or possibly planet formation (Armitage & Hansen 1999).…”
Section: Introductionmentioning
confidence: 73%
“…Following Equation 9 of Owen, Clarke & Ercolano (2012), the corresponding mass loss rate due to X-ray photoevaporation is ∼ 2 × 10 −8 M /yr, which is roughly a factor of 10 higher than the measured accretion rate for TW Hya. Owen et al (2010) predict that for a 0.7 M star and X-ray luminosity of 2 × 10 30 erg/sec X-ray photoevaporation will create a gap at ∼ 1 au, when the accretion rate falls to about a tenth of the wind rate.…”
Section: Evidence Of X-ray Photoevaporation In Tw Hyamentioning
confidence: 99%
“…This will change the density vertical structure of the disc; the density at the launching point of the photo-evaporative wind, which sets the mass-loss rate, might be affected. Although X-ray photo-evaporation has been shown to be quite resistant to changes in the underlying disc structure (Owen et al 2012b), it remains to be seen whether this applies also to such extreme differences. In particular, even if this effect is unlikely to change the total mass-loss rate, it will probably change the flow topology (Owen et al 2012b), which might have implications for the inner disc.…”
Section: Discussionmentioning
confidence: 99%
“…The details of the photoevaporation profile assumed can be found in the appendix of Owen et al (2012a). In our simulations we do not allow the planet to migrate, as Rosotti et al (2013) found migration to have little impact.…”
Section: Numerical Modelmentioning
confidence: 99%
See 1 more Smart Citation